Peningkatan Mutu Komunikasi Pemuda Yang Beretika Dan Cerdas Dengan Semangat Ajaran Veda - Ni Gusti Ayu Kartika (UHN IGB Sugriwa Denpasar, 2018)
In an attempt to build ethnic Hindu youth and ethnic youths who are ethical and intelligent according to Hindu teachings, Hindu youth must understand and apply the formula of Hindu teachings through understanding and application of Hindu philosophical teaching or tattwa or darsana, understanding and application of Hindu moral teachings, as well as appreciation and practice of the Hindu religious ceremony on a regular basis (nitya karma) as well as within the appointed time (naimitika karma). The three core formulations of the teachings of Hinduism according to the source in the Vedas, should be understood in full and berintegratif anatara one doctrine with other teachings that support each other and unite in implementation. The importance of Hindu youth to understand the meaning of the teachings of Hinduism through tattwa, also very useful also ethical or ethical Hindu material to be the basis of ground, apply, and berkarma, so that his movement leads to good deeds (susila or subhakarma). This is not the ideals of the Hindu youth, because the ideals of the Hindu youth are for the realization of wise young Hindu cadres (gunamantha), wisdom (prajna), intelligent wisesa), acting well (sadhu), doing right (sukarma or subhakarma ), diligent work (karmani) is not lazy to work (akarmani), apply full value (mulya karma), as well as being a good and right young (suputra-suputri).